Direct Writing of Flexible Barium Titanate/Polydimethylsiloxane 3D Photonic Crystals with Mechanically Tunable Terahertz Properties. Issue 7 (24th February 2017) - Zhu, Pengfei; Yang, Weiyi; Wang, Rong; Gao, Shuang; Li, Bo; Li, Qi
Abstract : Mechanically flexible 3D terahertz photonic crystals (3D‐TPCs) are created by the direct‐writing technology with a composite ink system composed of polydimethylsiloxane (PDMS) and barium titanate (BaTiO3 ) nanoparticles. The direct‐writing technology allows an easy creation of complex 3D structures with designed geometry, while the refractive indices of the composite ink can be modulated by varying the content of BaTiO3 nanoparticles. Thus, 3D‐TPCs with different terahertz properties are obtained by the direct‐writing technology. More interestingly, these 3D‐TPCs demonstrate a unique tunable terahertz property under external force field due to their mechanical flexibility from the PDMS matrix of the composite ink. Thus, their terahertz property is responsive to external force fields reversibly, which can find novel applications in terahertz technology and other related technological applications. Abstract : Mechanically flexible 3D terahertz photonic crystals are created by direct‐writing technology with a composite ink system composed of polydimethylsiloxane and barium titanate nanoparticles, which demonstrate a unique tunable terahertz property under external force field. Their terahertz property is responsive to external force fields reversibly, which can find novel applications in terahertz technology and other relative technological applications.